Antimicrobial and Toxicity Studies of Dodonaea aungustifolia Extracts‐Mediated Green Synthesized Copper Oxide Particles. Issue 8 (23rd February 2022) - Andra, Swetha; Balu, Satheesh kumar; Ponnada, Srikanth; Mohan, Sakar; Hossain, Md Shahadat; Sivakumar, Bharathkumar; Palanivel, Baskaran; Alsalme, Ali; Muthalagu, Murugesan
Abstract: In this study, copper oxide (CuO) particles have been synthesized through a green approach using Dodonaea aungustifolia (DA) extracts as a reducing agent, which is extracted using methanol (CuO‐DA(Mt)) and the mixture of aqueous + methanol solvents (CuO‐DA(Aq+Mt)). These green synthesized CuO particles have been analysed using XRD, FESEM, EDAX, TEM, DLS, and FTIR techniques. Further, these materials have also been investigated for their in‐vitro antioxidant, antibacterial, and hemolytic properties. The obtained results showed that the synthesized CuO‐DA(Aq+Mt) particles show excellent antibacterial and antioxidant properties. Similarly, the in‐vitro hemolytic assessment of CuO‐DA(Aq+Mt) show the improved non‐hemolytic activity at various concentrations as compared to CuO‐DA(Mt). From the results and observations, a plausible mechanism for the observed properties of these CuO particles have also been proposed. Abstract : This study demonstrates the synthesis of copper oxide (CuO) nanoparticles through the green‐chemistry approach using Dodonaea aungustifolia (DA) extract as a reducing agent, which is extracted using methanol (CuO‐DA(Mt)) and the mixture of aqueous + methanol solvents (CuO‐DA(Aq+Mt)). The CuO‐DA(Aq+Mt) nanoparticles showed excellent in‐vitro antioxidant, antibacterial, and anti‐hemolytic properties as compared to CuO‐DA(Mt), which showed that the solvent mixture of Aq+Mt better stabilizes the CuO NPs without deteriorating the features of the extract and biocompatibility/bioactivity of the CuO NPs.